Characteristics of community-acquired carbapenem-resistant Enterobacterales. (23rd July 2022) - Shrestha, Rima; Luterbach, Courtney L; Dai, Weixiao; Komarow, Lauren; Earley, Michelle; Weston, Gregory; Herc, Erica; Jacob, Jesse T; Salata, Robert; Wong, Darren; Anderson, Deverick; Rydell, Kirsten B; et al.
Abstract: Background: Community-acquired carbapenem-resistant Enterobacterales (CA-CRE) are an important threat. Methods: In CRACKLE-2, we defined patients with CA-CRE as admitted from home, without pre-existing conditions, and a positive culture within 48 h of admission. Healthcare-associated CRE (HA-CRE) were those with the lowest likelihood of community acquisition, not admitted from home and cultured >48 h after admission. Specific genetic markers in carbapenemase-producing Klebsiella pneumoniae were evaluated through random forest modelling. Results: CA-CRE and HA-CRE were detected in 83 (10%) and 208 (26%) of 807 patients. No significant differences were observed in bacterial species or strain type distribution. K. pneumoniae (204/291, 70%) was the most common CRE species, of these 184/204 (90%) were carbapenemase producers (CPKP). The top three genetic markers in random forest models were kpi_SA15, fimE, and kpfC . Of these, kpi_SA15 (which encodes a chaperone/usher system) was positively associated (OR 3.14, 95% CI 1.13–8.87, P  = 0.026), and kpfC negatively associated (OR 0.21, 95% CI 0.05–0.72, P  = 0.015) with CA-CPKP. Conclusions: Ten percent of CDC-defined CRE were CA. The true proportion of CA-CRE in hospitalized patients is likely lower as patients may have had unrecorded prior healthcare exposure. The kpi_SA15 operon was associated with the CA phenotype.